'Ear today gone tomorrow': routine neonatal ear canal cultures are not useful predictors of early onset invasive bacterial sepsis. (4th April 2011) - Battersby, A J; Webster, R; Neal, T; Subhedar, N
Abstract : Background: Culture of body surfaces including the ear canal, throat and rectum are often routinely performed on new neonatal unit admissions. It has been postulated that in the early postnatal period the neonatal ear canal may still contain amniotic fluid and thus be superior to other sites for identifying maternally acquired bacteria responsible for early onset neonatal bacterial sepsis. However, the evidence base for routine ear canal culture is limited. Objectives: (1) To ascertain whether ear canal cultures identify bacteria distinct from those in the throat and rectum. (2) To identify whether organisms isolated from the ear canal are responsible for invasive sepsis. (3) To establish whether ear canal cultures alter clinical management. Methods: We identified infants admitted to the level one neonatal unit over a 6 month period (April 2008–September 2008). Clinical data was obtained from the 'Badger' electronic patient data system and microbial data was obtained from the 'Telepath' microbiology laboratory database. Results: 601 infants were admitted to the neonatal unit during the study period. 66% of admissions (397/601) had ear canal cultures performed. 30.5% (121/397) of ear canal cultures were positive. 3% (3/121) of infants had organisms isolated from the ear canal but not the throat or rectum. However, none of these infants developed culture positive sepsis. 6.5% (24/397) of the infants with ear canal cultures developed blood culture positive early onset sepsis. The ear canals of 12.5% (3/24) of infants harboured the same organisms as isolated from the blood: two coagulase negative staphylococci and one group B streptococcus. These organisms were also isolated from the throat and rectum. No deviation from unit antibiotic policy was made and no barrier nursing was instigated as a consequence of ear canal culture results. Conclusions: On the basis of this small study, the neonatal ear canal does not appear to harbour organisms distinct from those in the throat or rectum. Ear canal cultures are not helpful in predicting the organisms responsible for invasive sepsis and should not guide clinical management. We recommend that the acquisition of admission ear canal cultures should not form part of routine clinical practice.